Peningkatan Kapasitas melalui Pelatihan Pembukuan Sederhana pada Depot Air Water di Binjai - Lores, Linda; Syahrial, Hery; Parulian, Tohap (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Simple bookkeeping training is an effort to improve the managerial capacity of Micro, Small, and Medium Enterprises (MSMEs), particularly in financial management. This community service activity was conducted at the Juli Water Depot in Binjai, which has not yet implemented a structured bookkeeping system. This lack of record-keeping makes it difficult for business owners to accurately assess their financial position, cash flow, and calculate profit and loss. The two-day training consisted of several stages: initial observation, material delivery, recording demonstrations, hands-on practice, mentoring, and evaluation. The materials provided covered the use of a Daily Cash Book, Operational Cost Recapitulation, and the preparation of a simple Profit and Loss Report. The training results demonstrated an increase in participants' knowledge and skills in recording daily transactions, identifying operational costs, and preparing simple financial reports. Participants also demonstrated a commitment to consistently implementing bookkeeping after the training. This training demonstrates that simple bookkeeping training is effective in helping MSMEs improve financial management, support more informed decision-making, and strengthen business sustainability.